Strength gains: block versus daily undulating periodization weight training among track and field athletes - Painter, K. B.; Haff, G. G.; Ramsey, M. W.; McBride, J.; Triplett, T.; Sands, W. A.; Lamont, H. S.; Stone, M. E.; Stone, M. H. (International Journal of Sports Physiology and Performance, 2012)
Recently, the comparison of "periodized" strength training methods has been a focus of both exercise and sport science. Daily undulating periodization (DUP), using daily alterations in repetitions, has been developed and touted as a superior method of training, while block forms of programming for periodization have been questioned. Therefore, the purpose of this study is to compare block to DUP in Division I track and field athletes. Thirty-one athletes were assigned to either a 10-wk block or DUP training group in which sex, year, and event were matched. Over the course of the study, there were 4 testing sessions, which were used to evaluate a variety of strength characteristics. Although performance trends favored the block group for strength and rate of force development, no statistically significant differences were found between the 2 training groups. However, statistically different (P = .05) values were found for estimated volume of work (volume load) and the amount of improvement per volume load between block and DUP groups. Based on calculated training efficiency scores, these data indicate that a block training model is more efficient than a DUP model in producing strength gains.